What makes a school a happy school? Portuguese students’ perspectives - Gramaxo, Patrícia; Flores, Isabel; Dutschke, Georg; Seabra, Filipa (Frontiers in Education, 2023)
UNESCO has sparked interest in the study of happy schools and, through its Happy Schools Project (HSP) framework, provides tools that enable the teaching and learning community to work towards making "happy schools" a reality. Since the understanding of happiness is culturally influenced (HSP studied Asian countries), we sought to identify parallels between the HSP framework and Portuguese schools through the eyes of students. To that end, we asked a group of Portuguese students to rate their happiness at school and answer three open questions: What makes you happy at school? What makes you unhappy at school? What is a happy school? Using an online survey, 2708 students participated in this study. We coded the answers with categories derived from the HSP framework, aiming to understand what characteristics students value most when referring to their happiness or unhappiness at school and what features a happy school should have. The findings show that most Portuguese students consider themselves to be reasonably happy. No relevant difference exists between boys' and girls' self-reported happiness levels, and their happiness decreases as age increases. Children emphasized relationships with friends and teachers and teachers' attitudes, competencies, and capacities as elements of a happy school. We found that school unhappiness is related to excessive workload and bullying. Even though there are cultural differences between countries, when we identified the characteristics of a happy school from the perspective of Portuguese students, we found similarities with the HSP framework guidelines.